2020
DOI: 10.1016/j.jfludis.2020.105793
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering therapy through telepractice in Turkey: A mixed method study

Abstract: Highlights Considering the quantitative findings, the telepractice and in-person groups showed a performance on an equivalent level. The greatest majority of the participants reported that they had adapted to telepractice and that this method was appropriate for them, despite barriers. For the clinician, loss of time, cost, and effort occurred more than expected for telepractice service. Some qualifications, such as experience, psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 49 publications
(115 reference statements)
3
15
0
11
Order By: Relevance
“…A study conducted by Eslami Jahromi et al [ 27 ] showed that there was a significant difference in the mean scores of stuttering severity before and after telepractice and more than half of the patients were satisfied with this treatment method. Similarly, Cangi and Togram [ 4 ] showed that telepractice is as effective as in-person therapy for adults who stutter. However, there is a debate regarding economic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Eslami Jahromi et al [ 27 ] showed that there was a significant difference in the mean scores of stuttering severity before and after telepractice and more than half of the patients were satisfied with this treatment method. Similarly, Cangi and Togram [ 4 ] showed that telepractice is as effective as in-person therapy for adults who stutter. However, there is a debate regarding economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although face-to-face healthcare delivery is considered a routine way of service delivery, sometimes accessing in-person speech therapy services can be difficult [ 4 ]. Hence, telepractice can be regarded as an alternative or supplemental model for care delivery and can provide healthcare services at the point of need [ 4 , 5 ]. Moreover, remote follow-up can cause the least inconvenience in patients’ daily routines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to acknowledge that comparisons of telepractice and traditional modalities are being conducted for a variety of other intervention targets. There were multiple studies that focused on coaching models for treatment, often for early-language intervention ( Akemoglu et al, 2020 ; Baharav & Reiser, 2020 ; Behl et al, 2017 ). These tended to report similar outcomes or improved outcomes when using telepractice compared with in-person delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also notable, international researchers are asking many similar questions ( Cangi & Toğram, 2020 ; Fairweather et al, 2016 ; McCarthy et al, 2012 ; Rao et al, 2018 ; Shprintzen & Golding-Kushner, 2012 ). In general, these studies have found telepractice outcomes consistent with or better than in-person delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data collected showed comparable outcomes between the two modes of delivery. Cangi and Toğram (2020) investigated the effectiveness of stuttering treatment delivered by telepractice on a sample of 20 adults who stutter, comparing it with the same treatment delivered in-person. This was a non-inferiority-controlled trial.…”
mentioning
confidence: 99%